2023
DOI: 10.1101/2023.03.03.530851
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The best plant-guarding ants in extrafloral nectaried plants and myrmecophytes according to baiting tests

Abstract: Extrafloral nectaried plants and myrmecophytes offer resources to ants that may engage in protective mutualisms. The role of different ant species in herbivore deterrence has long been analyzed by using herbivore baits, and ants are regarded as effective plant guards if they attack and/or remove the baits (mostly termites) from plants. Here, we conducted a comparative investigation on which ants display aggression toward baits, which ants are better plant guards, and which plants (extrafloral nectaried plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 73 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…In general, we propose a conceptual framework for understanding the impacts of different levels of ant aggressiveness on factors related to the protection and reproduction of plants; see [ 28 , 92 ]. Docile ants ( point a in Figure 3 ) with low levels of aggressiveness tend to show a low effect on protection effectiveness ( Figure 3 A), pollinator deterrence ( point a in Figure 3 B), and the probability of cross-pollination ( Figure 3 D) but high effects on self-pollination probability ( Figure 3 C) and pollen removal/deposition ( Figure 3 E).…”
Section: Optimal Ant Mutualist Partnersmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, we propose a conceptual framework for understanding the impacts of different levels of ant aggressiveness on factors related to the protection and reproduction of plants; see [ 28 , 92 ]. Docile ants ( point a in Figure 3 ) with low levels of aggressiveness tend to show a low effect on protection effectiveness ( Figure 3 A), pollinator deterrence ( point a in Figure 3 B), and the probability of cross-pollination ( Figure 3 D) but high effects on self-pollination probability ( Figure 3 C) and pollen removal/deposition ( Figure 3 E).…”
Section: Optimal Ant Mutualist Partnersmentioning
confidence: 99%
“…In this region, 25% of woody plant species and 30% of individuals at a site were found to have EFNs [ 93 , 94 , 95 ]. The main group of numerically and behaviorally dominant ants foraging on these plants is Camponotus [ 60 , 92 , 94 , 96 , 97 , 98 ], with great emphasis on C. crassus , which has been recorded as the most abundant and protective ant on EFN-bearing plants in different areas of the Brazilian savanna [ 2 , 63 , 64 , 68 , 92 , 94 , 96 , 97 , 99 ]. For instance, Souza et al [ 92 ] showed that Camponotus ants are the best EFN-bearing plant protectors according to baiting tests.…”
Section: Optimal Ant Mutualist Partnersmentioning
confidence: 99%
See 3 more Smart Citations